Low income and mobility: evidence from a migration choice model applied to India. (2nd January 2022) - Sangita, Seema
ABSTRACT: This paper sets out to investigate the effect of levels of income and ownership of assets on domestic migration. The inverted U theory points out that at low levels of incomes and wealth, households may not be able to afford the cost of migration, and hence, are left behind, leading to geographical poverty traps. This idea is tested using a household level migration choice model that attempts to explain outward migration by levels of income/wealth and other factors, including local amenities and social background. The inverted U theory breaks down at very low levels of income – there is a relatively higher probability of outward migration by households belongs to absolutely the lowest deciles of income. However, wealth, or lack thereof, does not have a similar effect on migration in this context.